2022
DOI: 10.3390/molecules27030902
|View full text |Cite
|
Sign up to set email alerts
|

Screening Wild Yeast Isolated from Cocoa Bean Fermentation Using Volatile Compounds Profile

Abstract: Yeasts are one of the main ingredients responsible for flavor precursors production associated with sensorial characteristics in chocolate. Using wild yeast isolated from cocoa beans fermentation is emerging as a strategy for developing starter cultures. However, the volatile compounds (VCs) produced by yeasts are not yet known. This study aimed to select wild yeasts with the potential to produce volatile compounds associated with desirable flavor attributes. A total of 150 wild yeasts strains were isolated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…The ester 2-pentanol acetate is a compound with fruity notes present in both fermentations at 48 h, which is similar to that reported by Cevallos-Cevallos et al [92]; in SC, its concentration remained relatively high until the end of fermentation compared to SF, which can be assumed that the yeast contributed to the formation of the compound (where its highest concentration was between 48 and 96 h). Regarding acids, one of the predominant compounds in SC was acetic acid (Table S4), which was similar to that reported by Chagas et al [99] and Sandoval-Lozano et al [100], which began to increase dramatically between 48 and 72 h of fermentation, a period in which it is associated with a conversion of ethanol to acetic acid, where the yeast S. cerevisiae contributes to the oxidation of alcohol [22,99,100]. A higher content of linalool could be observed in SC compared to SF, as reported by Assi-Clair et al [22]; our study showed high concentrations after 48 h of fermentation similar to Klis et al [101]; finally, a shorter presence of isobutyl acetate (48 h) was detected in SC, presenting floral, fruity and banana notes [102], as detected in the same type of fermentation in the study of Assi-Clair et al [22].…”
Section: Characterization Of the Profile Of Volatile Compounds (Vcs) ...supporting
confidence: 88%
“…The ester 2-pentanol acetate is a compound with fruity notes present in both fermentations at 48 h, which is similar to that reported by Cevallos-Cevallos et al [92]; in SC, its concentration remained relatively high until the end of fermentation compared to SF, which can be assumed that the yeast contributed to the formation of the compound (where its highest concentration was between 48 and 96 h). Regarding acids, one of the predominant compounds in SC was acetic acid (Table S4), which was similar to that reported by Chagas et al [99] and Sandoval-Lozano et al [100], which began to increase dramatically between 48 and 72 h of fermentation, a period in which it is associated with a conversion of ethanol to acetic acid, where the yeast S. cerevisiae contributes to the oxidation of alcohol [22,99,100]. A higher content of linalool could be observed in SC compared to SF, as reported by Assi-Clair et al [22]; our study showed high concentrations after 48 h of fermentation similar to Klis et al [101]; finally, a shorter presence of isobutyl acetate (48 h) was detected in SC, presenting floral, fruity and banana notes [102], as detected in the same type of fermentation in the study of Assi-Clair et al [22].…”
Section: Characterization Of the Profile Of Volatile Compounds (Vcs) ...supporting
confidence: 88%
“…Other yeasts found in cocoa formation that produce aromas are Galactomyces Galactomyces geotrichus and Wickerhamomyces anomalus (Koné et al 2016). Saccharomyces, Pichia, Hanseniaspora, Kluyveromyces, Hansenula, Wickerhamomyces and Torulaspora are the predominant wild genera of yeast in cocoa fermentation in Colombia (Sandoval-Lozano et al 2022).…”
Section: Non-alcoholic Fermented Beveragesmentioning
confidence: 99%
“…The main yeast species involved in different biotechnological applications worldwide is the ascomycete fungus Saccharomyces cerevisiae. However, several native yeasts species have been demonstrated to be also involved in the production of traditional food and beverages in Colombia, such as "kumis", "chicha", and "champus", among others [14,[100][101][102].…”
Section: Food and Beverages From Fungimentioning
confidence: 99%